O5.3. IMPAIRED LEFT TEMPORAL-PARIETAL JUNCTION FMRI ACTIVITY DURING CATEGORY FLUENCY IN FIRST-EPISODE PSYCHOSIS. (18th May 2020) - Perumaly, Leana; Curtis, Mark; Fishel, Vanessa; Torrence, Natasha; Wang, Yiming; Seebold, Dylan; Farris, Rebekah; Coffman, Brian; Salisbury, Dean
Abstract: Background: Language impairments are a core feature of schizophrenia. Category fluency is severely impacted, even as early as the first-episode of psychosis (FEP). It remains unclear which brain regions in the early course of schizophrenia are dysfunctional during category fluency. Therefore, we investigated differences in fMRI bold activity during a category fluency task in FEP, with particular attention to left temporo-parietal junction (TPJ) and inferior frontal gyrus (IFG), areas critical to verbal fluency. Our hypothesis was that left TPJ would show overactivity in FEP due to functional dysconnectivity with IFG, thought to modulate TPJ activation. Methods: Twenty-seven FEP and 25 matched healthy controls (HC) completed an overt category fluency task (animal naming) from the MATRICS Consensus Cognitive Battery (MCCB), and a covert category fluency task while BOLD fMRI was acquired. The fMRI task had a total of 10 blocks (30s duration) with two alternating conditions: category and rest. At the beginning of the category condition, a category name (birds, breeds of dogs, fruits and vegetables, fish, flowers and trees) was displayed on the screen, and individuals were instructed to think of items within that category. At the beginning of the rest condition, individuals were instructed to silently repeat the word "rest" to themselves. To isolate the activity related to category exemplar generation, the rest condition and the category condition fMRI data were contrasted using SPM12. An uncorrected cluster-defining primary threshold of p<.001 was used at the voxel level, and an FWE correction was used at the cluster level to correct for multiple comparison. Results: FEP (47.3±12.1) were significantly less fluent compared to HC (55.8±11.3) in the overt MCCB category fluency task (p =.017). In the fMRI covert fluency task, several regions were activated during the category condition (FWE p<.05), primarily including regions in the language network (IFG and TPJ). The left TPJ activation interacted between groups (pFWE-corr =.016). During the category task, HC deactivated left TPJ, whereas FEP did not. Discussion: FEP have impaired overt category fluency performance, and appear to have deficient deactivation in a region of the left TPJ language area during a category fluency task. TPJ is thought to communicate with Wernicke's area to translate thoughts into words. Temporal language areas are also thought to be deactivated by IFG during verbal fluency tasks. This fMRI finding is consistent with dysconnectivity between IFG and TPJ during verbal fluency, although future work is needed to definitively address this possible network dysfunction.